Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 1887 species occurrences available in GBIF matching the query: { "and" : [ "Country is Spain", { "or" : [ "TaxonKey is Ceropegia fusca Bolle", "TaxonKey is Ceropegia hians Svent.", "TaxonKey is Allagopappus viscosissimus Bolle", "TaxonKey is Andryala webbii (Christ) A.Santos", "TaxonKey is Argyranthemum adauctum (Link) Humphries", "TaxonKey is Argyranthemum broussonetii (Balb. ex Pers.) Humphries", "TaxonKey is Argyranthemum callichrysum (Svent.) Humphries", "TaxonKey is Argyranthemum coronopifolium (Willd.) Humphries", "TaxonKey is Argyranthemum foeniculaceum (Willd.) Webb, 1840", "TaxonKey is Argyranthemum frutescens (L.) Sch.Bip.", "TaxonKey is Argyranthemum haouarytheum Humphries & Bramwell", "TaxonKey is Argyranthemum hierrense Humphries", "TaxonKey is Argyranthemum escarrei (Svent.) Humphries", "TaxonKey is Argyranthemum sventenii Humphries & Aldridge", "TaxonKey is Argyranthemum webbii Sch.Bip.", "TaxonKey is Artemisia ramosa Buch, 1819", "TaxonKey is Carduus baeocephalus Webb & Berthel.", "TaxonKey is Carlina falcata Svent.", "TaxonKey is Carlina texedae Marrero Rodr.", "TaxonKey is Carlina xeranthemoides L.fil.", "TaxonKey is Cheirolophus sventenii (A.Santos) G.Kunkel", "TaxonKey is Cheirolophus teydis (C.Sm.) G.López", "TaxonKey is Erigeron cabrerae Dittrich", "TaxonKey is Gonospermum canariense (DC.) Less.", "TaxonKey is Gonospermum gomerae Bolle" ] } ] } The dataset includes 1887 records from 61 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001547-150721130643939/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences